Comprehensive Energy, Exergy, and Environmental Assessment of a Tri-Generation Biomass System Integrating Gasification, Anaerobic Digestion, and Solid Oxide Fuel Cell - Mohammadian, Mehran; Motallebzadeh, Roghayyeh; Ghafouri, Jafar; Javani, Nader (JIHAD DANESHGAHI, 2025)
Global warming presents a significant challenge, largely driven by carbon dioxide emissions from conventional power generation. Renewable energy technologies, particularly biomass-integrated systems, provide a promising pathway to mitigate these emissions sustainably. This study conducts a comprehensive energy, exergy, and environmental assessment of a tri-generation biomass system incorporating gasification, anaerobic digestion, and a Solid Oxide Fuel Cell (SOFC). Two configurations are examined: one utilizing syngas from gasification and the other biogas from anaerobic digestion. The results show that the biogas-based system achieves a superior exergy efficiency of 44.22%, compared to 39.18% for the gasification-based system, while also reducing CO2 emissions by 0.072 tons/MWh. Additionally, optimizing the fuel utilization factor (0.76 for the digester-SOFC and 0.78 for the gasifier-SOFC) significantly enhances system performance. These findings underscore the environmental benefits of biogas in tri-generation systems and provide valuable insights into optimizing biomass-based energy solutions.
Keywords: Biomass energy; Gasification; Anaerobic digestion; Solid oxide fuel cell; Exergy analysis, CO2 mitigation; TRIGENERATION SYSTEM; GASIFIER; HEAT; Chemistry; Engineering